A pre-post study to assess the impact of an information-problem solving intervention on university students’ perceptions and self-efficacy towards search engines - Parissi, Marioleni; Komis, Vassilis; Lavidas, Konstantinos; Dumouchel, Gabriel; Karsenti, Thierry (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2019)
This study investigates the changes in university students’ perceptions towards the use of Web search engines after their exposure to a teaching intervention centered on the information problem-solving process. A total of 138 students of the Department of Educational Sciences and Early Childhood Education of the University of Patras were surveyed to measure perceived ease of use and usefulness of search engines and search engine self-efficacy. A questionnaire, part of which was based on the Technology Acceptance Model, was developed and distributed to respondents, both before and after the course, to measure their perceptions. The results revealed statistically significant improvement for the ease of use and usefulness of search engines, as well as for search engine self-efficacy.